The Effects of Pyrolysis Temperature and Time to The Quality of Coconut (Cocos Nucifera) Midrib Liquid Smoke - Yulia, Ruka; Pria, Wahyu Ana; Hakim, Lukmanul; Makmur, Teuku (International Conference on Multidisciplinary Research, 2020)
The aim of this study was to determine the effect of pyrolysis temperature and pyrolysis time on thequality of liquid smoke of coconut midribs waste such as yield, pH, acetic acid, phenol. The method of thisresearch was the descriptive method. The variables of this study were pyrolysis time of 2 hours and 3hours and pyrolysis temperature of 200, 250, 300, 350, 400 oC with two repetitions. The result showedthat the best condition of coconut midrib liquid smoke was on the pyrolysis temperature of 400 oC, for 3hours pyrolysis time resulted in yield, pH, acetic acid and phenol of liquid smoke were 24%, 2.53, 6,45ppm, 3,76 ppm. The increase in pyrolysis time and temperature was also found to increase the yield,phenol, acetic acid, and pH. Keywords: Pyrolysis, liquid smoke, coconut midribs